Comparative Theoretical Analysis of Biomass and Energy Potentials of Usable Maize and Wheat Stalk Wastes: Example of Sakarya Province - Muhammed Taşova; İsmail Naneli (Turkish Journal of Agriculture: Food Science and Technology, 2020)
With the increase in the population in the world and in our country, the energy requirement related to consumer demands is constantly increasing. In our country, although wind, sun, etc. energy sources are used in energy production, fuels of fossil origin (coal, natural gas, oil etc.) are used more in energy production. Renewable energy sources, which are alternative due to the decrease in fossil fuel reserves, negative environmental effects and inability to meet the energy needs in the future, come to the fore. In this study, Turkey Statistical Institute (TUIK) according to the 2015-2019 year data, Sakarya at the central and districts in cultivation areas for cultivated of using the amounts of maize and wheat product (da) average waste, dry matter, and volatile dry matter, methane and energy their potential has been determined. As a result of the calculations, it has been determined that the maize sap waste amount has the highest 25695.68 tons of waste and 201197.15 MJ energy potential in Adapazarı district in 2017. Among the wheat stalk wastes, in 2017, Geyve district had the highest 269.95 tons of waste and 2113.72 MJ energy respectively.